The Effect of Work Motivation and Work Discipline on Employee Performance in A Communication Company in The Medan Region - Raysa Vionika (Yayasan Multidimensi Kreatif, 2024)
This study aims to examine the influence of motivation and work discipline on the performance of employees of Communication Company, Tbk Telkom Medan Business Area, which has a number of research samples from employees at Communication Company, Tbk Telkom Medan Business Area. This study uses multiple linear regression analysis with data processing using SPSS version 25.0. The results of the study can be found if work motivation has a positive and partially significant effect on employee performance with the value of the t-coefficient calculated >ttable, 4.410 >1.670 at a significant 0.0 < 0.05, then work discipline has a positive and partially significant effect on employee performance with the value of thet-coefficient calculated > t table, 4.841 > 1.670 at a significant 0.0 <0.05, then work motivation and work discipline have a positive and significant effect simultaneously on employee performance with a coefficient value Fcalculated > Ftable, 28.685 > 2.76 at a significant 0.00 < 0.05, with The magnitude of the determination coefficient is 0.531 or 53.1% and it can be said that the relationship between the independent variable and the strongly bound variable is strong. While the rest is in other factors.